PEDOT-MnO2 Based Nanocomposite for Supercapacitor Application - Shamsun Nahar, Sultana (My University, 2025)
Key objective of this study was to develop a high-performance electrode material by integrating a conductive polymer (PEDOT) and a transition metal oxide (MnO2). Individual MnO2 and PEDOT electrodes were synthesized as well, to compare the electrochemical behavior of the composite. Herein, we have used an anionic surfactant, sodium dodecyl sulfate (SDS) to enhance the surface morphology of individual MnO2, PEDOT and PEDOT-MnO2 based nanocomposites. 1 M Na2SO4 was used as an electrolyte in a three-electrode setup to perform the electrochemical characterizations. For the electrochemical setup, Ag/AgCl was used as a reference electrode, and graphite foil acts both as working electrode (WE), and counter electrode (CE). The electro-polymerization process was carried out in a potential window of 0 to 1 V with 20 cycles, and a scan rate of 50mV/s using cyclic voltammogram (CV). To reveal the chemical structure, bonding interaction, and surface morphology Raman spectroscopy, FTIR spectroscopy and scanning electron microscopy (SEM) was done respectively. Cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), electrochemical impedance spectroscopy (EIS), employed to find out the electrochemical properties. In this work, the specific capacitance of the nanocomposite was 222 mF/cm2, the capacitance retention value was 65%, and after 1000 cycles, it achieved this stable capacitance retention. Therefore, all these characterizations performed in this work indicate that the synergistic combination of PEDOT and MnO2 can improve the capacitive behavior and can be utilized in supercapacitor-type energy storage applications.
Keywords: Supercapacitor, PEDOT, MnO2, electrochemical process